2019
DOI: 10.3390/su11216084
|View full text |Cite
|
Sign up to set email alerts
|

Nonmarketization Bargaining and Actual Compensation Level for Land Requisition: A Qualitative Comparative Analysis of China’s Land Requisition Conflict Events

Abstract: In the land requisition market in China, two very different compensation levels for land requisition can be seen in the real world: one is the highly rigid official compensation level for land requisition and the other is a fuzzy actual compensation level for land requisition. In order to uncover the determinants of the actual compensation level for land requisition in China, this paper adopts Qualitative Comparative Analysis (QCA) to analyze the causal relationship between nonmarketization bargaining factors,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…In this study's sample, except for the very small number of pilot-county respondents, the reported renting behavior should be regarded as non-public gray trading of agricultural housing use rights without formal approval [56]. Such behavior inevitably conflicts with the management responsibilities of village cadres, thus intensifying the conflict between them and the villagers [57]. In the Pearl River Delta region of China, there exists a specific type of community named "village in city" (between villages and cities), which is featured by rural governance and urban community governance.…”
Section: Village Governance Factorsmentioning
confidence: 99%
“…In this study's sample, except for the very small number of pilot-county respondents, the reported renting behavior should be regarded as non-public gray trading of agricultural housing use rights without formal approval [56]. Such behavior inevitably conflicts with the management responsibilities of village cadres, thus intensifying the conflict between them and the villagers [57]. In the Pearl River Delta region of China, there exists a specific type of community named "village in city" (between villages and cities), which is featured by rural governance and urban community governance.…”
Section: Village Governance Factorsmentioning
confidence: 99%
“…While the process of transferring the ownership of rural land from the collective to the state is administratively transparent (being legally governed by strict policies), yet how future revenue from the sale of this land is to be shared or distributed is highly opaque. Therefore there is a growing literature detailing rent‐seeking behavior and corrupt practices (Song et al., 2016, 2020) by village leaders and the ensuing conflicts which occur (Huang et al., 2019; Jay Chen, 2020; Song et al., 2016) from these land‐lost farmers. The role that village leaders play in resolving conflicts and carrying out rural land requisition for urban development is therefore of paramount importance for understanding rural land resettlement in China.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, many land use transitions have taken place over wild areas both from the dominant morphology and recessive morphology with the quantity, spatial structure, and function change of land use and land cover [13][14][15]. On the one hand, land use transitions are largely driven by different land use types representing the benefits of different departments conflicting in space and will lead to a new balance of regional land use morphology patterns [16,17].On the other hand, land use transitions may trigger new land use conflicts during transformations between different land use types and allocation of land resources due to policy and institutional failures [14,18]. Thus, exploring the spatiotemporal characteristics of land use conflicts is an important research topic to enhance the understanding of the human-nature relation and provide critical insights into the dynamics of land use transitions.…”
Section: Introductionmentioning
confidence: 99%